2019
DOI: 10.1111/gcb.14799
|View full text |Cite
|
Sign up to set email alerts
|

Methane emissions from contrasting urban freshwaters: Rates, drivers, and a whole‐city footprint

Abstract: Global urbanization trends impose major alterations on surface waters. This includes impacts on ecosystem functioning that can involve feedbacks on climate through changes in rates of greenhouse gas emissions. The combination of high nutrient supply and shallow depth typical of urban freshwaters is particularly conducive to high rates of methane (CH4) production and emission, suggesting a potentially important role in the global CH4 cycle. However, there is a lack of comprehensive flux data from diverse urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 58 publications
9
27
0
Order By: Relevance
“…We assume that NH 4 is essentially a signal of agricultural/urban run‐off, which will deliver high inputs of N, P and labile organic matter into waterbodies thus fuelling CH 4 production. There were significantly higher CH 4 fluxes in waterbodies with the largest TP concentrations, in keeping with a wide body of literature showing higher emissions in nutrient‐rich waterbodies including ditches and artificial ponds (Audet et al, 2020; Beaulieu et al, 2019; Herrero Ortega et al, 2019; Ollivier et al, 2019a; Peacock et al, 2017, 2019; Webb, Hayes, et al, 2019). However, high TP concentrations did not guarantee high fluxes, and this is in agreement with a recent synthesis of ditch CH 4 emissions (Peacock et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We assume that NH 4 is essentially a signal of agricultural/urban run‐off, which will deliver high inputs of N, P and labile organic matter into waterbodies thus fuelling CH 4 production. There were significantly higher CH 4 fluxes in waterbodies with the largest TP concentrations, in keeping with a wide body of literature showing higher emissions in nutrient‐rich waterbodies including ditches and artificial ponds (Audet et al, 2020; Beaulieu et al, 2019; Herrero Ortega et al, 2019; Ollivier et al, 2019a; Peacock et al, 2017, 2019; Webb, Hayes, et al, 2019). However, high TP concentrations did not guarantee high fluxes, and this is in agreement with a recent synthesis of ditch CH 4 emissions (Peacock et al, 2021).…”
Section: Discussionsupporting
confidence: 77%
“…There were significantly higher CH 4 fluxes in waterbodies with the largest TP concentrations, in keeping with a wide body of literature showing higher emissions in nutrient-rich waterbodies including ditches and artificial ponds (Audet et al, 2020;Beaulieu et al, 2019;Herrero Ortega et al, 2019;Ollivier et al, 2019a;Peacock et al, 2017Peacock et al, , 2019Webb, Hayes, et al, 2019). However, high TP concentrations did not guarantee high fluxes, and this is in agreement with a recent synthesis of ditch CH 4 emissions (Peacock et al, 2021 Note: Soil type had a significant effect on CO 2 concentrations (p < 0.001, d = 0.71, effect size = medium) and CH 4 concentrations (p = 0.041, d = 0.19, effect size = very small).…”
Section: Drivers Of Ghg Concentrations and Fluxessupporting
confidence: 86%
“…CH 4 fluxes from both streams to vary between 0.08 and 7.02 mmol m −2 d −1 are within the literature range (Crawford, Lottig, et al, 2014;Stanley et al, 2016;Striegl et al, 2012). We confirmed that although streams are well-aerated, CH 4 oversaturation is ubiquitous in the DOC-rich boreal (Campeau & Giorgio, 2014;Natchimuthu et al, 2017;Rasilo et al, 2017) and temperate streams (Herrero Ortega et al, 2019;Hope et al, 2001;Jones & Mulholland, 1998b;Schrier-Uijl et al, 2011;Smith & Böhlke, 2019). Halbedel and Koschorreck (2013) estimated CO 2 emissions from both streams between 23 and 355 mmol m −2 d −1 with higher CO 2 emission rates in the Hassel stream (252 ± 53 mmol m −2 d −1 ).…”
Section: Ch 4 Emissionssupporting
confidence: 86%
“…Other studies have found that water chemical properties are not always good predictors for CH 4 concentrations or uxes in aquatic systems (Ortega et al 2019). Apart from nutrient and substrate availability in the water column, the nutrient status of the sediment is important for methanogenesis.…”
Section: Drivers Of Ditch Ch 4 Emissionsmentioning
confidence: 94%